Management of Islamic Boarding School Education in Instilling The Character of Santri - Laela Rahmawati; Mukhtar Latif; Kemas Imron Rosadi (Nazhruna: Jurnal Pendidikan Islam, 2022)
This article aims to determine the educational management of An-Nur Islamic Boarding Schools, to determine the character of students who are implanted, to determine the educational management of Islamic Boarding Schools in instilling the character of students, to determine the supporting and inhibiting factors in instilling the character of students at the An-Nur Islamic Boarding School. The purpose of this research is to add insight into the educational management of Islamic Boarding Schools in instilling the character of students, as an evaluation material in instilling character education in Islamic boarding schools. This research is qualitative research with a survey method carried out at the An-Nur Islamic Boarding School, Tangkit Village, using a qualitative approach. Sources of data from this research are the results of observations of researchers, interviews, and documentation. Based on the process of data collection and analysis, the researcher can conclude several things. First, the management of the An-Nur is divided into two parts, namely the nurturing section and the teaching section. Second, the characters instilled are religious, honest, disciplined, independent, appreciating, achievement, Friendly/Communicative, love for peace, care for the environment, hard work, democratic, curiosity, love to read, and responsible.